Pendekatan Teoritikal dalam Sosiologi Hukum terhadap Dinamika Kepatuhan Masyarakat - Nugraha Gading Priandana; Muhammad Rizky Al-Farizi; Ira Kurniawan; Lanang Maulana; Rhaina Rifka Nefindia; Salma Tabina; Muhammad Mona Adha; Febra Anjar Kusuma; Putut Ary Sadewo (INDO PUBLISHING, 2026)
This study analyzes the dynamics of legal compliance in society through a theoretical approach in sociology of law. Legal compliance is influenced not only by normative rules but also by social structures, cultural values, and individual perceptions. This research employs a qualitative descriptive method using a literature review of recent academic publications. The findings indicate that legal compliance is a multidimensional phenomenon shaped by legal awareness, legitimacy, social structures, and the compatibility between formal law and living law. Classical theories from Durkheim, Weber, and Ehrlich are integrated with modern perspectives to explain the complexity of legal behavior in society. The study reveals that compliance based on internalization is more sustainable than compliance based on coercion. Furthermore, the effectiveness of law depends on public trust and legitimacy. Therefore, sociological approaches are essential in legal development to create responsive and socially accepted laws.